Development of stability indicating, validated single dissolution method for simultaneous estimation of clopidogrel bisulfate and rivaroxaban in tablet dosage formulation by RP-HPLC method - Sajjanwar, Rupali; Bhaskaran, Shyamala; Kakati, Kulesh; Jha, Shailendra Kumar (Journal of Applied Pharmaceutical Research, 2015)
A dissolution method was developed for combination of two drugs which are already marketed as an individual product, Clopidogrel Bisulfate Tablets USP 75 mg and another is Rivaroxaban Tablets 10 mg & 20 mg. It was emphasized that both products have several advantages when given as combination therapy. Hence, the preference was given to develop a single dissolution method for the analysis of both the active components. This article presents a single dissolution method to accommodate both drugs. The method uses USP Type II Apparatus (paddles) at 75 rpm in 1000 mL of Acetate buffer (pH 4.5) medium containing 1% Sodium Lauryl Sulfate as surfactant at 37 °C± 0.5°C . This dissolution methodology provides good dissolution profiles for both Clopidogrel Bisulfate and Rivaroxaban and is able to discriminate the changes in composition, manufacturing process and stability for the combination tablets. To quantitate both drugs simultaneously, a rapid isocratic reversed-phase liquid chromatographic method was developed and validated.